A recyclable thermoset with built-in thermocleavable group developed from a cis-cyclobutane-1, 2-dicarboxylic acid. Issue 63 (18th July 2022) - Wang, Zhihan; Amjaour, Houssein; Robertson, Joseph E. M.; Azizov, Djavdat; Ugrinov, Angel; Chu, Qianli R.
Abstract : A novel class of recyclable thermoset has been developed from cis -3, 4-diphenylcyclobutane-1, 2-dicarboxylic acid (CBDA-4) due to its thermocleavability at high temperature. Abstract : A novel class of recyclable thermoset has been developed from cis -3, 4-diphenylcyclobutane-1, 2-dicarboxylic acid (CBDA-4) due to its thermocleavability at high temperature. This key CBDA-4 building block was synthesized from β- trans -cinnamic acid using a [2+2] photocycloaddition reaction. CBDA-4 was subsequently linked with glycerol via esterification to give a thermoset with T g of 68 °C. The thermoset was heated to 300 °C to analyze its degradation. A key intermediate was successfully obtained after purification of the degraded polymer. NMR, FT-IR, HRMS, and single crystal X-ray diffraction confirmed the intermediate was glycerol cinnamate, which was the result of splitting cyclobutane in the polymer backbone at high temperature. Glycerol cinnamate was readily hydrolyzed reforming the starting materials glycerol and trans -cinnamic acid to complete the recycling loop.